KRISTAL HEMOGLOBIN PADA BERCAK DARAH YANG TERPAPAR DENGAN BEBERAPA SABUN ANTISEPTIK CAIR MENGGUNAKAN TES TEICHMANN DAN TES TAKAYAMA - Syarifah Rabiatul Adawiah; Enikarmila Asni; Mohammad Tegar Indrayana (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTForensic investigation was not only done to investigate injuries sustained by the victim of crime, but also to investigate objects or other evidences, such as blood, in crime scene. Some forensic investigation that can confirm if suspected object is blood was confirmatory test (Teichmann and Takayama test). The criminals often wipe out blood using antiseptic liquid soap. In that case, it may give different description in forensic investigation. Therefore, the aim of this study was to know the description of hemoglobin crystal on bloodstain that exposed by antiseptic liquid soap with Teichmann and Takayama test. This study was experimental study with pre-test post-test design. There were 18 bloodstain slides as sample of this study, including 2 control slides and 16 slides that had been exposed with 4 antiseptic liquid soap brands. This study showed 18 bloodstain slides (100%) had positive result after exposed by using Teichmann and Takayama test and there were no changes of crystal’s shape. It could be conclude that hemoglobin crystal still could be found in bloodstain that exposed by antiseptic liquid soap with Teichmann and Takayama test.Keyword : bloodstain, hemoglobin crystal, antiseptic liquid soap , Teichmann, Takayama